Storage Capacity Analysis On The Construction Of Reservoir C Faculty Of Medicine University Of Lampung - mukti, Bayu krishna; kusumastuti, dyah indriana; jokowinarno, dwi (Universitas Lampung, 2021)
Reservoir is a basin that can be utilized to contain excess rain water which will be used during dry season and it is also an act of effort to nurture the existence and sustainability of the environment, nature and the ground water, so that the water can always be available in an adequate quantity and quality to fulfill the needs for the living. reservoir is also utilized to maintain the quality of the water ground and as an ecotourism object as well. In University of Lampung, there are several reservoirs that can be found, one of which is reservoir C which is located at the faculty of medicine, University of Lampung. The main purpose of this research is to find out the capacity storage of the reservoir by using several supporting softwares to simplify the calculation. the supporting softwares which are used in this research are AutoCAD 2017, Microsoft Excel 2017, and Google Earth Pro. The outputs of this research are (1) The estimation of flood discharge at reservoir C faculty of medicine, University of Lampung (2) The storage capacity of the reservoir C faculty of medicine, University of Lampung based on this research, it can be concluded that reservoir is qualified as a conservation reservoir which has 6594.9909 m 3 storage capacity.